The Use of Social Media by the Nigerian Masses to Voice the Opinions of the Oppressed: A Case Study of #EndSARS Campaign 2020 - Gesah, Benjamin Lornder (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
From the analysis of this research data and the raw tweets used in this study, it is clear that the EndSARS was a success and now stand out as the most significant protests ever in Nigeria's history, and most especially social media, and by the youths. The protests succeeded in bringing the government down on its knees despite her long silence. While the government was pressured to finally wind off the dreaded police unit (SARS) on October 11, 2020, the shooting to death of unarmed protesters at Lekki Toll Plaza may be a devil's gift in exchange for SARS disbandment. This study focuses on social media choice for oppressive activism in Nigeria using the #EndSARS Campaign of 2020 as a case study. The research analyses how the Nigerian youth used Twitter to initiate, coordinate and protest online and on the streets of Nigeria and cities around the globe to demand that the government brings an end to all manner of police brutality and exclusion from the running of the country‟s government. This study adopts a qualitative method, with a thematic approach to analyze the data and documents how the youth used Twitter to coordinate and carry out the protests. Building on the New Social Movements and Deleuze & Guattari‟s Rhizomatic theories, the study captures the youth's displeasure over their leaders' impunity for the past decades. To carefully explore the research questions, this study carefully analyses the data, using predefined themes of Brutality in the face of Democracy and Technology, Surveillance and Censorship, amongst others. The findings reveal that celebrities, world personalities, and social media influencers were the #EndSARS protests' driving forces. While there was no leadership and organizational structures, the protesters themselves coordinate their activities flawlessly. Therefore, the study commended Nigeria's government for disbanding the dreaded police unit, SARS, launching a reformation of the police force and creating a youth fund for the youth to access at a low-interest term. Worthy of commendation is the Judicial Commission instituted to look into cases of brutality against the Nigeria Police and other security forces. Finally, the study made recommendations to address future agitations.

ÖZ: Bu çalışma, Nijerya'daki siyasi aktivizm için sosyal medya seçimine odaklanıyor ve #EndSARS 2020 kampanyasını bir vaka çalışması olarak ele alıyor. Araştırma, Nijerya‟daki gençliğin, polis vahşetine son verilmesini ve ülkedeki hükümetin yönetiminden dışlanmasını talep etmek ve protestolarını yürütmek için hem Nijerya sokaklarında ve dünyanın dört bir yanındaki şehirlerde, hem de sosyal medyada Twitter'ı nasıl kullandığını analiz ediyor. Bunun yanında, çalışma, gençlerin protestolarını koordine etmek ve gerçekleştirmek için Twitter'ı nasıl kullandığını, veri ve belgelere bağlı olarak tematik bir yaklaşımla nitel bir yöntem kullanarak incelemektedir. Yeni Toplumsal Hareketler ve Deleuze‟nin Rhizomatic teorilerine dayanan bu çalışma, gençlerin son yıllarda liderlerinin cezasız kalması konusundaki memnuniyetsizliğini de ele alıyor. Araştırma soruları dikkatlice seçilmiş olan bu çalışmada, demokrasi, teknoloji, gözetleme ve sansür karşısında önceden tanımlanmış olan vahşet temaları da kullanılarak veriler ayrıntılı bir şekilde analiz edilmiştir. Elde edilen bulgular, ünlülerin, dünyaca ünlü kişilerin ve sosyal medya fenomenlerinin #EndSARS adlı protestoların en kuvvetli itici güçleri olduğunu ortaya koyuyor. Liderleri ve örgütsel yapılanmaları olmamasına rağmen, tüm protestocular faaliyetlerini kusursuz bir şekilde koordine etmeyi başardılar. Koordine edilen protestolar ve çalışmalar, Nijerya hükümetinin korkunç olarak tanımlanan polis birimi SARS'ı dağıttığı, polis gücünde bir reform başlattığı ve gençlerin erişmesi için bir gençlik fonu yarattığı için övgüye değer bulunmuştur. Polise ve diğer güvenlik güçlerine yönelik şiddet olaylarını incelemek için kurulan Yargı Araştırma Panellerinden de övgüye bahsedilmektedir. Çalışma, gelecekte ortaya çıkabilecek çalkantıları ve olası problemleri ele almak için de önerilerde bulunmuştur.
Master of Arts in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2021. Supervisor: Assoc. Prof. Dr. Metin Ersoy
Keywords: Communication and Media Studies Department; Political participation--Political Parties--Use of--Social Media--Nigeria Internet in political campaigns--Political Activism--Nigeria Social Media--Facebook--Political aspects--Nigeria Political Communication--Election Campaigns; Activism, Social Media, Police Brutality, EndSARS, Nigerian Youth, Twitter